O financiamento dos partidos políticos no Brasil - Pereira, Carolina Canhassi (2022)
This paper presents a study about the financing of political parties in Brazil. The financing aims to fund routine party activities as well as those aimed at capturing the vote during the electoral period. The financing model of Brazilian political parties is plural, with the combination of public and private resources. Currently, after the Electoral Reform of 2015, which sought to mitigate the influence of economic power in the reach of political power, the financing became predominantly public, with the investment of large amounts of resources from the Party Fund and the Electoral Fund. Despite successive electoral reforms that try to improve the financing system, resousing corruption, inequality and misuse of financial resources in election campaigns, account transparency and the real accounting of political parties is still a sensitive issue that deserves attention from the legislation. Social and judicial controls are the essential tools for the effectiveness of the system and the effective punishment of parties and candidates who collect or spend their resources in an obscure manner outside the law. In addition to the investment in information technology, the improvement of the Electoral Justice depends on the expansion of its internal surveillance structure. The collection of financial resources in the electoral dispute is inevitable and will occur anyway, but what will lead to the conduct of candidates within the legal parameters is the effectiveness of control and the certainty of punishmen